Inulin supplementation improves some inflammatory indices, clinical outcomes, and quality of life in rheumatoid arthritis patients - Ali Tabatabaeyan; Ani Grigorian; Mansour Salesi; Awat Fiezi; Marzieh Kafeshani (Scientific Reports)
Abstract Rheumatoid arthritis (RA) is a multifactorial autoimmune disease that causes joint dysfunction and is associated with changes in serum levels of some biomarkers. The present study investigated the effect of inulin supplementation on pain intensity, clinical outcomes, and quality of life in patients with RA.In a randomized, triple-blind, parallel clinical trial, 60 patients over 18 years of age with RA were randomly assigned to receive either 10 g of inulin or maltodextrin per day for 8 weeks. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels were assessed using biochemical kits at the beginning and end of the study. Clinical outcomes were also evaluated, including morning stiffness and pain intensity measured by the Visual Analog Scale (VAS), hand grip measured by a sphygmomanometer (Seca), disease activity assessed using the Disease Activity Score 28 (DAS-28), and overall quality of life determined by the Health Assessment Questionnaire (HAQ).The number of swollen joints, tender joints, pain intensity, and DAS-28 significantly decreased in both groups. However, hand grip, morning stiffness, ESR, CRP, and HAQ improved significantly only in the intervention group. After the intervention, in the intervention group compared to the control group, serum CRP levels significantly decreased (P = 0.02), while serum ESR levels showed no significant reduction (P = 0.45). The number of tender joints (P = 0.002), the number of swollen joints (P = 0.04), DAS-28, HAQ, morning stiffness, and hand grip strength (P = 0.02) significantly improved, but pain intensity did not change (P = 0.11).Inulin appears to benefit inflammatory status, disease activity, and clinical outcomes in patients with rheumatoid arthritis. Incorporating it into their treatment protocol could be valuable for managing their condition. Trial registration: Our study was approved in the Iranian Registry of Clinical Trials ( www.irct.ir ) on 10/5/2023, with the registration number IRCT20230506058098N1.